2004
DOI: 10.1096/fj.03-0038com
|View full text |Cite
|
Sign up to set email alerts
|

Increases in estrogen receptor‐α concentration in breast cancer cells promote serine 118/104/106‐independent AF‐1 transactivation and growth in the absence of estrogen

Abstract: A common phenotype in breast cancer is the expansion of the estrogen receptor-alpha (ER+) cell population and an inappropriate elevation of ERalpha protein, the latter predisposing patients for a poorer prognosis than those with lower levels of the receptor. A tetracycline-inducible ERalpha overexpression model was developed in the MCF-7 cell line to assess induction of endogenous gene activation and growth in response to elevations in ERalpha protein. Heightened levels of ERalpha resulted in aberrant promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 69 publications
6
66
0
Order By: Relevance
“…It has been shown that steroid receptors, particularly those expressed in tumors, may become activated in the absence of cognate ligands (Weigel et al, 1995;Blaustein, 2004;Fowler et al, 2004). The data presented herein suggest that the same may be true for the AhR.…”
Section: Discussionsupporting
confidence: 57%
“…It has been shown that steroid receptors, particularly those expressed in tumors, may become activated in the absence of cognate ligands (Weigel et al, 1995;Blaustein, 2004;Fowler et al, 2004). The data presented herein suggest that the same may be true for the AhR.…”
Section: Discussionsupporting
confidence: 57%
“…PRL-induced binding of ERa to the promoter determines co-activator recruitment and histone acetylation, both landmarks of receptor-mediated transcriptional activation. Increased ERa levels are common in breast cancer (Fabris et al, 1987;Holst et al, 2007) and have been associated with aberrant promoter occupancy, increased gene expression and cell proliferation in the absence of hormonal stimulation (Fowler et al, 2004). Because it has been reported that PRL increases ERa levels in breast cancer cells (Shafie and Brooks, 1977;Gutzman et al, 2004a), the stimulatory effect of PRL on the ER target genes could be due to ERa induction.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were transiently transfected with the expression vector for HA-tagged human ERα, pUHD10-3-ER-HA, generously provided by Elaine T. Alarid, Department of Physiology, University of Wisconsin-Madison [33]. Cells were plated at 20,000 cells per well in a six-well plate in standard media containing LIF on day 0.…”
Section: Transfectionmentioning
confidence: 99%